A note on how to realize the full potential of the EU-SILC data - Melissa Berger; Sandra Schaffner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The European Union Statistics on Income and Living Conditions (EU-SILC) is a rotational panel provided by Eurostat that covers variables with a high potential for comparative European labour market and social research. Unfortunately, its current availability limits its potential research applications. This research note describes these shortcomings of the current data provision. Furthermore, we make two contributions for a better exploitation of these data sets: First, we develop a method for combining the different waves in order to increase the number of usable observations; and second, we indicate how monthly data on income and hourly pay can be derived.
urn:nbn:de:bsz:180-madoc-387483
Keywords: C81; C83; D31; 330; EU-SILC; sampling weights; income; Europe; data quality; panel data